Telitacicept in combination with B-cell depletion therapy in MuSK antibody-positive myasthenia gravis: a case report and literature review - Wang, Jia; Zheng, Haotao; Wei, Jia; Wu, Jiaping; Feng, Ziyang; Chen, Xueqin; Liu, Yangsicheng; Qin, Wenxin; Qin, Xiude; Kong, Fanxin (Frontiers in Immunology, 2024)
Muscle-specific kinase (MuSK) myasthenia gravis (MG) is relatively rare and has a higher incidence of myasthenic crisis compared with other subtypes. However, there is still a lack of effective treatment for refractory MuSK MG. We report the case of a 70-year-old female MuSK MG patient with recurrent fluctuations who stabilized on telitacicept in combination with anti-CD20 B-cell depletion therapy. This combination regimen deserves further investigation. Furthermore, we summarized the treatment protocols of 14 previously reported cases of MuSK MG.